A wear-resistant and impact-resistant bionic structure composite coating and preparation method thereof

By adopting a unique alternating layered structure of soft and hard layered structure in the coating, a combination of eutectic high-entropy alloy and ceramic materials, combined with laser cladding technology, the wear resistance and drag reduction performance of the existing coating under extreme operating conditions is solved. The problem is that it achieves efficient impact, wear and corrosion resistance, and is suitable for offshore equipment and other fields.

CN117684163BActive Publication Date: 2024-12-24GUANGDONG INST OF NEW MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311779675.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2024-12-24
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

The existing soft and hard phase bionic structural coatings still need to be further improved in terms of wear resistance and resistance reduction performance, especially in extreme operating conditions, which cannot effectively protect equipment components.

Method used

Using a unique horizontal and vertical direction alternating soft and hard "brick-mud" imitation shell layered structure design, combined with AlCoCrFeNi eutectic high-entropy alloy and high-hardness ceramic material, composite coating is prepared through laser cladding additive manufacturing technology. The FCC and BCC biphasic structure is formed and ceramic particles are introduced into the coating to enhance hardness and toughness.

Benefits of technology

It has achieved excellent impact, wear and corrosion resistance of the coating, enhanced the long-term service capability of equipment parts, and has good engineering application value. It is especially suitable for offshore equipment, rail transit and metallurgy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117684163B_ABST
    Figure CN117684163B_ABST
Patent Text Reader

Abstract

The present invention provides a wear-resistant and impact-resistant bionic structure composite coating and a preparation method thereof, wherein the wear-resistant and impact-resistant bionic structure composite coating comprises at least one bionic structure layer composed of a first strip made of a soft material and a second strip made of a hard material, wherein the bionic structure layers are arranged perpendicularly to each other, and the width surface and the length surface of the bionic structure layer of the upper end surface and / or the lower end surface thereof are located on the same plane, wherein the soft material is an AlCoCrFeNi eutectic high entropy alloy, and the hard material is a composite material of an AlCoCrFeNi eutectic high entropy alloy + ceramic particles. The composite coating has excellent impact resistance, wear resistance and corrosion resistance through a unique horizontal and vertical soft and hard alternating "brick-mud" shell-like layered structure design and a dual-phase eutectic high entropy alloy and high-hardness ceramic material design, and has good engineering application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical fields of surface engineering, new materials and high-end equipment manufacturing, and in particular to a wear-resistant and impact-resistant bionic structure composite coating and a preparation method thereof. Background Art

[0002] With the rapid development of industry and science and technology, the development and utilization of modern marine resources have put forward increasingly stringent requirements on equipment. For example, key parts of equipment such as deep-sea drilling tools, shield machine cutters, and mixer blades need to serve for a long time under extreme conditions of corrosion, wear, and impact. At present, the base materials of key components have reached a certain performance limit. If they are required to serve reliably and for a long time in harsh environments, it is necessary to further study important technical guarantees such as component surface coating technology. Traditional surface coating technologies such as thermal spraying and electroplating have relatively low bonding strength. After long-term impact and mechanical action, they are prone to failure and cannot play a protective role. Laser cladding additive manufacturing technology has become an effective means of preparing wear-resistant and impact-resistant coatings due to its controllable thickness, high metallurgical bonding strength, and diverse materials.

[0003] In order to meet the needs of survival, organisms in nature constantly adapt to the environment and adjust their body surface morphology during evolution, creating a variety of soft and hard morphologies and structures with excellent drag reduction and wear resistance. Soft and hard alternating bionic structural materials refer to the soft and hard alternating surface morphology of organisms, with materials with small elastic modulus as soft materials and materials with large elastic modulus as hard materials, and are arranged in an orderly or disordered manner in a certain ratio. The design of soft and hard alternating bionic structural materials involves many aspects. Differences in material properties, structural forms, material ratios, basic dimensions, etc. will affect the properties of the materials. Reasonable design is the basis for ensuring that soft and hard alternating bionic structural materials have corresponding characteristics.

[0004] Chinese patent CN115747791A "Self-generated wear-resistant coating with alternating distribution of soft and hard phases, preparation method and workpiece thereof" discloses a wear-resistant coating with alternating distribution of soft and hard phases, but the coating only achieves alternating distribution of soft and hard phases on the horizontal plane, and its wear resistance and drag reduction performance still needs to be further improved.

[0005] Therefore, it is of great significance to develop a wear-resistant and impact-resistant bionic structural composite coating with excellent wear resistance and drag reduction performance and a reasonably designed soft and hard bionic structure and a preparation method thereof. Summary of the invention

[0006] In view of the problem that the wear resistance and drag reduction performance of the existing soft and hard phase alternating distribution coatings still needs to be further improved, the present invention provides a wear-resistant and impact-resistant bionic structure composite coating. Through the unique horizontal and vertical soft and hard alternating "brick-mud" shell-like layered structure design and dual-phase eutectic high entropy alloy and high-hardness ceramic material design, it has excellent impact resistance, wear resistance and corrosion resistance, has good engineering application value, and has good application prospects in marine engineering equipment, rail transit, metallurgy and other fields.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A wear-resistant and impact-resistant bionic structural composite coating, comprising at least one bionic structural layer, wherein any one of the bionic structural layers and the bionic structural layers on its upper end surface and / or lower end surface are arranged perpendicular to each other, and the width surface of the bionic structural layer and the length surface of the bionic structural layer on its upper end surface and / or lower end surface are located on the same plane;

[0009] The bionic structure layer comprises a first strip made of a soft material and a second strip made of a hard material;

[0010] The length of the first stripe and the second stripe of any one of the bionic structure layers corresponds to the width of the first stripe and the second stripe of the bionic structure layer on its upper end surface and / or lower end surface;

[0011] The soft material is an AlCoCrFeNi eutectic high entropy alloy, and the hard material is a composite material of an AlCoCrFeNi eutectic high entropy alloy and ceramic particles.

[0012] Furthermore, the bionic structure layer is provided with three layers, and the three bionic structure layers are respectively a bottom layer, a middle layer and a surface layer which are stacked in sequence from bottom to top.

[0013] Furthermore, the bionic structure layer has N first strips, and the bionic structure layer has N+1 second strips, wherein N≥1; the N first strips and the N+1 second strips are alternately arranged on the same horizontal plane.

[0014] Furthermore, the ceramic particle contents of the bottom layer, middle layer and surface layer composite materials are 5-15wt.%, 20-30wt.%, and 40-60wt.% respectively.

[0015] Furthermore, the total thickness of the composite coating is 2.5-3.5 mm, and the thickness ratio of the bottom layer, the middle layer and the surface layer is 1:(0.8-1.1):(0.8-1.1).

[0016] Furthermore, the first strip and the second strip in the bionic structure layer have the same height and length, and a width ratio of 1:(1.5-2).

[0017] Furthermore, the AlCoCrFeNi eutectic high entropy alloy has a two-phase structure of FCC and BCC, and the content ratio of the two phases FCC and BCC is 2:1.

[0018] Furthermore, the AlCoCrFeNi eutectic high entropy alloy comprises the following components in atomic percentage: 15%-18% Al, 15%-18% Co, 15%-18% Cr, 15%-18% Fe, 30%-37% Ni, and the remainder is unavoidable impurities.

[0019] The ceramic particles are one or more of WC, SiC, Al2O3, Cr3C2, and the particle size of the ceramic particles is 40-90 μm.

[0020] Another object of the present invention is to provide a method for preparing a wear-resistant and impact-resistant bionic structure composite coating.

[0021] A method for preparing the above-mentioned wear-resistant and impact-resistant bionic structural composite coating comprises the following steps:

[0022] S1. AlCoCrFeNi high entropy alloy and ceramic particle powders were mixed for 40-60min according to the required ratio, ball milled to obtain composite powders of different ratios for standby use;

[0023] S2. Preheat the pretreated part substrate using an electromagnetic induction device at a preheating temperature of 200-350°C;

[0024] S3. Prepare the coating layer by layer on the surface of the part by laser cladding. Each layer is clad on the soft material area first and then on the hard material area. The additive manufacturing direction of the next layer is rotated 90° relative to the previous layer. The laser power is 1600-2600W, the spot diameter is 3-5mm, the powder feeding rate is 25-30g / min, the laser scanning rate is 8-12mm / s, and the overlap rate is 40%-60%;

[0025] S4. The clad parts are subjected to annealing heat treatment at 300-400° C. for 3 hours to form the wear-resistant and impact-resistant bionic structural composite coating.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The AlCoCrFeNi eutectic high entropy alloy in the wear-resistant and impact-resistant bionic structural composite coating of the present invention has a unique FCC and BCC two-phase layered composite structure, has good toughness and impact and corrosion resistance, but the hardness needs to be improved. The use of high-hardness ceramic particles can further enhance the hardness of the eutectic high-entropy alloy material and improve its wear resistance. The effective combination of AlCoCrFeNi eutectic high entropy alloy and high-hardness wear-resistant ceramic particles, plus the good wetting effect and matching of the two, lays a good material foundation for the strong and tough integration of the eutectic high-entropy alloy-ceramic composite coating. At the same time, the design of the bionic multi-layer structure with interlaced layers ensures that the pattern of "soft and hard alternating" and "strong and tough" is presented on a macro scale; the strong material has high strength to ensure the strength of the coating to resist the external impact and improve the impact resistance, and the tough material has excellent plasticity and plastic deformation ability, which can delay the external impact, and form a heterogeneous interface layer at the junction of the strong material and the tough material. Such an interface layer can hinder the growth of cracks caused by external impact, so that when the cracks expand disorderly in the complex structure of soft and hard metal overlap and interweave, they will produce repeated deflections due to the different strengths of the materials on both sides of the densely distributed interweaving interface, thereby achieving the purpose of consuming a large amount of fracture energy and absorbing external impact energy.

[0028] (2) The wear-resistant and impact-resistant bionic structural composite coating of the present invention has a unique horizontal and vertical soft and hard alternating "brick-mud" shell-like layered structure design and a dual-phase eutectic high entropy alloy and high-hardness ceramic material design, which enables the coating to have excellent impact resistance as well as excellent wear resistance and corrosion resistance.

[0029] (3) The wear-resistant and impact-resistant bionic structural composite coating of the present invention utilizes the advantages of additive manufacturing to manufacture the composite coating through laser cladding. The substrate is first preheated and then cladding is performed, which greatly enhances the element interaction between the cladding layer with added high-hardness ceramic material and the substrate, improves wettability, and reduces stress concentration at the junction of the coating and the substrate, thereby avoiding defects such as cracking; and selects specific laser cladding parameters to ensure that the energy absorbed by the material can fully melt it, avoiding the poor forming quality caused by the failure of the coating and the substrate to form a good metallurgical bond, and at the same time, avoids powder splashing during the laser cladding process, causing some metal elements to be ablated or vaporized, thereby affecting the coating forming quality and performance, and can realize integrated rapid manufacturing of the composite coating, which has the advantages of customization, high production efficiency, high material utilization, low production cost, good forming quality, excellent interface bonding, high stability, etc., has good engineering application value, and has good application prospects in the fields of marine engineering equipment, rail transit, metallurgy, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0031] Figure 1 It is a schematic diagram of a wear-resistant and impact-resistant bionic structural composite coating; figure numbers: 1-base material; 2-second strip; 3-first strip; 4-WC ceramic particles; 5-bottom layer; 6-middle layer; 7-surface layer.

[0032] Figure 2 This is a path planning diagram for laser additive preparation of a wear-resistant and impact-resistant bionic structural composite coating; a-soft material path design; b-hard material path design; the arrow represents the additive manufacturing direction.

[0033] Figure 3 This is a microstructure diagram of the eutectic high entropy alloy in the wear-resistant and impact-resistant bionic structural composite coating of Example 1.

[0034] Figure 4 This is a microstructure diagram of the eutectic high entropy alloy-WC ceramic particles in the wear-resistant and impact-resistant bionic structural composite coating of Example 1. DETAILED DESCRIPTION

[0035] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0036] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0037] Example 1

[0038] A method for preparing a wear-resistant and impact-resistant bionic structure composite coating comprises the following steps:

[0039] S1. AlCoCrFeNi high entropy alloy (16.5% Al, 16.5% Co, 16.5% Cr, 16.5% Fe, 34% Ni) and 40-90 μm WC ceramic particle powders were mixed for 60 min and ball-milled to obtain composite powders of different proportions for standby use according to the required proportions of the three-layer ceramic particles of 15wt.%, 30wt.% and 60wt.% respectively;

[0040] S2. Process the part substrate to a suitable size, and perform preliminary treatments such as grinding, decontamination, and sandblasting on the surface; plan the laser cladding path according to the surface geometry of the parts, set each layer to clad the soft material area first and then the hard material area, and the additive manufacturing direction of the next layer is rotated 90° relative to the previous layer; use an electromagnetic induction device to preheat the pretreated part substrate at a preheating temperature of 300°C;

[0041] S3. Laser cladding was performed on the surface of the parts layer by layer to prepare the coating. The total coating thickness was 3 mm, the thickness ratio of the bottom layer, the middle layer and the surface layer was 1:1:1, the laser power was 1800 W, the spot diameter was 4 mm, the powder feeding rate was 25 g / min, the laser scanning rate was 10 mm / s, and the overlap rate was 50%;

[0042] S4. The clad parts are subjected to annealing heat treatment at 300° C. for 3 hours, and are machined to obtain the desired size, thereby forming the wear-resistant and impact-resistant bionic structural composite coating.

[0043] Example 2

[0044] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0045] Compared with Example 1, the hard material of each layer is a composite material of AlCoCrFeNi eutectic high entropy alloy + ceramic particles, and the contents of the three layers of ceramic particles are 10wt.%, 25wt.% and 50wt.% respectively.

[0046] Example 3

[0047] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0048] Compared with Example 1, the hard material of each layer is a composite material of AlCoCrFeNi eutectic high entropy alloy + ceramic particles, and the contents of the three layers of ceramic particles are 5wt.%, 20wt.% and 40wt.% respectively.

[0049] Example 4

[0050] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0051] Compared with Example 1, the ceramic particles in the composite coating are Cr3C2.

[0052] Example 5

[0053] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0054] Compared with Example 1, the width ratio of the soft material and the hard material alternately distributed in the layer channels of the bottom layer, the middle layer and the surface layer is 1:1.5.

[0055] Example 6

[0056] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0057] Compared with Example 1, the laser cladding process parameters of step S3 are as follows: laser power 2600 W, spot diameter 5 mm, powder feeding rate 30 g / min, laser scanning rate 12 mm / s, overlap rate 50%.

[0058] Comparative Example 1

[0059] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0060] Compared with Example 1, the material of each layer in this comparative example is AlCoCrFeNi eutectic high entropy alloy.

[0061] Comparative Example 2

[0062] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0063] Compared with Example 1, the material of each layer in this comparative example is WC ceramic particles.

[0064] Comparative Example 3

[0065] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0066] Compared with Example 1, each layer of this comparative example is a composite material of AlCoCrFeNi eutectic high entropy alloy + ceramic particles, and the contents of the three layers of ceramic particles are 20wt.%, 40wt.% and 60wt.% respectively.

[0067] Comparative Example 4

[0068] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0069] Compared with Example 1, each layer of this comparative example is a composite material of AlCoCrFeNi eutectic high entropy alloy + ceramic particles, and the contents of the three layers of ceramic particles are 10wt.%, 20wt.% and 40wt.%, respectively. The preparation path of the composite coating remains consistent, and there is no 90° staggered path in the horizontal direction.

[0070] Comparative Example 5

[0071] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0072] Compared with Example 1, the coating material of this comparative example is a single-layer AlCoCrFeNi eutectic high entropy alloy.

[0073] Comparative Example 6

[0074] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0075] Compared with Example 1, the coating material of this comparative example is a composite material of a single layer of 40 wt.% AlCoCrFeNi eutectic high entropy alloy + 60% WC ceramic particles.

[0076] Comparative Example 7

[0077] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0078] Compared with Example 1, the coating material of this comparative example is a single-layer WC ceramic particle material.

[0079] Comparative Example 8

[0080] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0081] Compared with Example 1, the part substrate is not preheated in step S2 of this comparative example.

[0082] Comparative Example 9

[0083] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0084] Compared with Example 1, the laser cladding process parameters of this comparative example S3 are: laser power 1200W.

[0085] Comparative Example 10

[0086] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0087] Compared with Example 1, the laser cladding process parameters of this comparative example S3 are: laser power 3200W.

[0088] Comparative Example 11

[0089] A method for preparing a wear-resistant and impact-resistant bionic structural composite coating, the steps not specifically described are the same as those in Example 1, except that:

[0090] Compared with Example 1, the laser cladding process parameters of this comparative example S3 are: scanning speed 20 mm / s.

[0091] The above samples were subjected to performance tests, and the experimental test methods were as follows:

[0092] Test method for coating forming quality: Determined in accordance with the national standard "GB / T 36591-2018"

[0093] Test method for wear weight loss: Determined in accordance with the national standard "GB / T 12444-2006"

[0094] Test method for self-corrosion current density: Determined in accordance with the national standard "GB / T 40299-2021"

[0095] Impact energy test method: Determined in accordance with the national standard "GB / T 2423.5"

[0096] Among them, the wear loss weight indicates the wear resistance of the coating. The smaller the value, the better the wear resistance of the coating. The self-corrosion current density indicates the corrosion resistance of the coating. The smaller the value, the better the corrosion resistance of the coating. The impact work indicates the impact resistance. The larger the value, the better the impact resistance of the coating.

[0097] The test results of Examples 1-6 and Comparative Examples 1-11 are shown in the following table:

[0098] Table 1 Test results of Examples 1-6 and Comparative Examples 1-11

[0099]

[0100]

[0101] It can be seen from Table 1 that the weight loss from abrasion in each embodiment of the present invention is less than 0.020 g, and the lowest self-corrosion current density can reach 2.458×10 -8 A / cm 2The impact energy is all above 100 J, which has outstanding comprehensive performance compared with the comparative examples, indicating that the wear-resistant and impact-resistant bionic structural composite coating of the present invention has excellent wear resistance, corrosion resistance and impact resistance.

[0102] However, since only a single material is used in Comparative Examples 1 and 2, the comprehensive performance is greatly reduced, especially in Comparative Example 2 which only uses WC ceramic particles, the self-corrosion current density is high, the impact work is only 35J, and the impact resistance is far inferior to that of the embodiments; the ceramic particle content in the hard material of Comparative Example 3 exceeds the range, the wear weight loss is high, and the impact resistance is poor; Comparative Example 4 has no staggered paths, and the comprehensive performance is acceptable, but cannot be compared with the embodiments; Comparative Examples 5, 6, and 7 change the single-layer material, and the comprehensive performance decreases in turn; Comparative Examples 8, 9, 10, and 10 change the laser cladding preparation method, and the resulting composite coating has poor forming quality, many defects, and poor wear resistance, corrosion resistance, and impact resistance.

[0103] In summary, the wear-resistant and impact-resistant bionic structural composite coating of the present invention effectively combines AlCoCrFeNi two-phase eutectic high entropy alloy and high-hardness wear-resistant ceramic particles, and the unique horizontal and vertical soft and hard alternating "brick-mud" shell-like layered structure design of the interlaced bionic multi-layer structure makes the coating have excellent impact resistance, as well as excellent wear resistance and corrosion resistance. At the same time, the advantages of additive manufacturing are utilized to manufacture the composite coating through laser cladding, and the substrate is first preheated and then clad, which greatly enhances the element interaction between the cladding layer with added high-hardness ceramic material and the substrate, improves wettability, and reduces stress concentration at the junction of the coating and the substrate. , thereby avoiding defects such as cracking; and selecting specific laser cladding parameters to ensure that the energy absorbed by the material can make it fully melt, avoid the coating and the substrate not forming a good metallurgical bond resulting in poor forming quality, and at the same time avoid powder splashing during the laser cladding process, causing some metal elements to ablate or gasify, thereby affecting the coating forming quality and performance. It can realize the integrated rapid manufacturing of composite coatings, with the advantages of customization, high production efficiency, high material utilization, low production cost, good forming quality, excellent interface bonding, high stability, etc. It has good engineering application value and has good application prospects in marine engineering equipment, rail transit, metallurgy and other fields.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A wear-resistant and impact-resistant bionic structural composite coating, characterized in that: It comprises at least one bionic structure layer, wherein any one of the bionic structure layers and the bionic structure layer on its upper end surface and / or lower end surface are arranged perpendicularly to each other, and the width surface of the bionic structure layer and the length surface of the bionic structure layer on its upper end surface and / or lower end surface are located on the same plane; The bionic structure layer comprises a first strip made of a soft material and a second strip made of a hard material; The soft material is an AlCoCrFeNi eutectic high entropy alloy, and the hard material is a composite material of AlCoCrFeNi eutectic high entropy alloy + ceramic particles; The bionic structure layer is provided with three layers, and the three layers of the bionic structure layer are a bottom layer, a middle layer and a surface layer which are stacked in sequence from bottom to top; The ceramic particle contents of the bottom layer, the middle layer and the surface layer composite materials are 5-15wt.%, 20-30wt.%, and 40-60wt.% respectively; It is prepared by the following preparation method, comprising the following steps: S1. AlCoCrFeNi high entropy alloy and ceramic particle powders were mixed for 40-60min according to the required ratio, ball milled to obtain composite powders of different ratios for standby use; S2. Preheat the pretreated part substrate using an electromagnetic induction device at a preheating temperature of 200-350°C; S3. Prepare the coating layer by layer on the surface of the part by laser cladding. Each layer is clad on the soft material area first and then on the hard material area. The additive manufacturing direction of the next layer is rotated 90° relative to the previous layer. The laser power is 1600-2600W, the spot diameter is 3-5mm, the powder feeding rate is 25-30g / min, the laser scanning rate is 8-12mm / s, and the overlap rate is 40%-60%; S4. The clad parts are subjected to annealing heat treatment at 300-400° C. for 3 hours to form the wear-resistant and impact-resistant bionic structural composite coating.

2. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The bionic structure layer has N first strips, and the bionic structure layer has N+1 second strips, wherein N≥1; the N first strips and the N+1 second strips are alternately arranged on the same horizontal plane.

3. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The total thickness of the composite coating is 2.5-3.5 mm, and the thickness ratio of the bottom layer, the middle layer and the surface layer is 1:(0.8-1.1):(0.8-1.1).

4. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The first strip and the second strip in the bionic structure layer have the same height and length, and the width ratio is 1:(1.5-2).

5. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The AlCoCrFeNi eutectic high entropy alloy has a two-phase structure of FCC and BCC, and the content ratio of the two phases FCC and BCC is 2:

1.

6. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The AlCoCrFeNi eutectic high entropy alloy comprises the following components in atomic percentage: 15%-18% Al, 15%-18% Co, 15%-18% Cr, 15%-18% Fe, 30%-37% Ni, and the remainder is inevitable impurities.

7. A wear-resistant and impact-resistant bionic structural composite coating according to claim 1, characterized in that: The ceramic particles are one or more of WC, SiC, Al2O3, Cr3C2, and the particle size of the ceramic particles is 40-90 μm.